2008
DOI: 10.1128/jb.00407-08
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Charged Residues at the C Terminus of MotA and N Terminus of MotB Are Important for Function of the Escherichia coli Flagellar Motor

Abstract: MotA contains a conserved C-terminal cluster of negatively charged residues, and MotB contains a conserved N-terminal cluster of positively charged residues. Charge-altering mutations affecting these residues impair motility but do not diminish Mot protein levels. The motility defects are reversed by second-site mutations targeting the same or partner protein.The MotA 4 MotB 2 complex of Escherichia coli is the stator of the rotary flagellar motor (5) and the H ϩ channel that couples the proton motive force to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…We speculate that PlzA or a PlzA-regulated factor(s) may modulate the function of a motor protein, perhaps by modulating the MotB proton channel. A recent study with E. coli reported that amino acid residues K53 to T64 of MotB act as a plug to prevent proton flow before the MotA-MotB complex associates with the flagellar structure (31,32). Because in plzA cells the swarming motility is attenuated but the swimming pattern was not altered, it appears likely that PlzA acts as a positive regulator in B. burgdorferi motility or chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that PlzA or a PlzA-regulated factor(s) may modulate the function of a motor protein, perhaps by modulating the MotB proton channel. A recent study with E. coli reported that amino acid residues K53 to T64 of MotB act as a plug to prevent proton flow before the MotA-MotB complex associates with the flagellar structure (31,32). Because in plzA cells the swarming motility is attenuated but the swimming pattern was not altered, it appears likely that PlzA acts as a positive regulator in B. burgdorferi motility or chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…MotB from R. sphaeroides has 366 residues, and remarkable differences were detected when it was compared to the E. coli MotB sequence (29). In fact, from the alignment of the MotB sequences of these bacteria, it can be observed that the similarity is restricted mainly to the C-terminal region while the region proposed as the MotB channel plug is not conserved in R. sphaeroides.…”
Section: Discussionmentioning
confidence: 96%
“…The occurrence of the motB(L149V) and motB(N278K) suppressor mutations in the periplasmic region of MotB of the pseudorevertants, which are located rather away from the proton pathway, implies that these mutations restore the motor function by acting indirectly rather than by altering the protonconducting pathway directly. As proper positioning of the MotA/B complex relative to the rotor would require a defined conformation of the C-terminal periplasmic domain of MotB (17)(18)(19), the reduced energy-coupling efficiency caused by the D33E mutation may be restored by modifications in the geometrical coupling of the rotor-stator interaction.…”
Section: Discussionmentioning
confidence: 99%